2009
DOI: 10.1021/nl8037294
|View full text |Cite
|
Sign up to set email alerts
|

Icosahedral Face-Centered Cubic Fe Nanoparticles: Facile Synthesis and Characterization with Aberration-Corrected TEM

Abstract: Iron nanoparticles are highly desirable for their potential applications in magnetic and catalytic industry. However, their shape-controlled fabrication is still an important challenge. Here we successfully synthesized icosahedral face-centered cubic (fcc) Fe nanoparticles with size of 5-13 nm by a specifically designed thermodynamic governed synthetic route, which is facile but highly efficient and reproducible. With the aberration-corrected transmission electron microscopy (TEM), the unique icosahedral struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
76
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 31 publications
7
76
0
Order By: Relevance
“…For the particle shown in Figure 1 d, its threefold axis was oriented perpendicular to the supporting TEM grid. [21] The inset shows a corresponding schematic drawing of an icosahedron in the threefold orientation. Our z-potential measurements indicate that Au icosahedra synthesized with NVP were negatively charged, with potentials ranging from À22 mV to À32 mV.…”
Section: Resultsmentioning
confidence: 99%
“…For the particle shown in Figure 1 d, its threefold axis was oriented perpendicular to the supporting TEM grid. [21] The inset shows a corresponding schematic drawing of an icosahedron in the threefold orientation. Our z-potential measurements indicate that Au icosahedra synthesized with NVP were negatively charged, with potentials ranging from À22 mV to À32 mV.…”
Section: Resultsmentioning
confidence: 99%
“…An intriguing example are tens of nanometers large Co nanoparticles stabilized in the fcc phase at ambient conditions while bulk Co crystallizes in hexagonal close-packed (hcp) structure [4,7]. Besides cooling, other preparation routes like high-pressure torsion, milling, epitaxial growth, chemical reduction, and microwave irradiation have been proven fruitful to stabilize pure metals in non-equilibrium crystalline phases of their phase diagram (e.g., fcc Fe nanoparticles [8][9][10], fcc Co films [11]) or to reveal unique crystalline phases, i.e., phases not * stesch@kth.se † xiaoqli@kth.se known from their pressure-temperature phase diagram (e.g., nanoparticles of fcc Ru [12], fcc Zr [13], tetragonal Ag [14], fcc Hf [15], and bcc Co films [16]). The common interest that drives current research on such nanostructured materials is related to their potentially shape-or size-enhanced mechanical, magnetic, optical, electronic, or catalytic properties [17].…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [109] observed the crystal phase evolution of Fe-Pt alloys from fcc to face-centered tetragonal (fct) at high temperature during the synthesis. Afterwards, under controlled synthetic conditions, hexagonal close-packed (hcp, 2H type) and 4H Au, [87,110] body-centered tetragonal (bct) Ag [111], fcc Fe [112], hcp Ni [113], fcc Ru [114] and hcp Rh [99] nanostructures can be prepared. In addition, during some typical growth stages such as seed growth, ligand exchange, and metal coating, the unusual phase or phase evolution can be also observed.…”
Section: Phase Evolutionmentioning
confidence: 99%